Searching for Sheboygans: On the future of small market newspapers. (April 2020) - Ali, Christopher; Radcliffe, Damian; Schmidt, Thomas R; Donald, Rosalind
This article addresses the knowledge gap regarding small market newspapers in the United States. We address a deceptively simple research question: what is the state of small market newspapers in the United States as seen through the eyes of practitioners and industry experts? Based on in-depth interviews with experts and practitioners, we argue for a more nuanced vocabulary to describe newspapers and local news. Grouping all newspapers into a monolithic industry – as general sector analyses often do – suggests a homogeneous experience. That is not the case. Smaller publications face their own challenges and opportunities, and they define success and innovation on their own terms. This reality needs to be better understood.